2019
DOI: 10.1590/2177-6709.24.5.040-045.oar
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of palate area before and after rapid maxillary expansion, using cone-beam computed tomography

Abstract: Objective: The aim of this study was to estimate the changes in the palate area after rapid maxillary expansion (RME) with the Hyrax expander in growing subjects, using cone beam computed tomography (CBCT). Methods: Fourteen patients (9 girls and 5 boys; mean age = 11.7 ± 2.4 years) who required RME as part of their orthodontic treatment were included in this study. CBCT records had been taken before RME treatment (T0), at the end of active expansion (T1) and after a 6-month retention period (T2). The CBCT sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 25 publications
3
10
0
4
Order By: Relevance
“…These ndings agree partially with the ones present in literature on patients with maxillary constriction [39][40][41][42][43] and con rm that RME signi cantly increases transversal dimensions of the palatal vault. However, to our knowledge, no study associated the RME to a decrease in the palatal depth.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These ndings agree partially with the ones present in literature on patients with maxillary constriction [39][40][41][42][43] and con rm that RME signi cantly increases transversal dimensions of the palatal vault. However, to our knowledge, no study associated the RME to a decrease in the palatal depth.…”
Section: Discussionsupporting
confidence: 92%
“…However, to our knowledge, no study associated the RME to a decrease in the palatal depth. On the contrary, Bruder C. et al, 43 demonstrated that maxillary constricted patients treated by RME have no vertical alteration of the palate. This result is in contrast with the one of our study.…”
Section: Discussionmentioning
confidence: 98%
“…Numerous authors have already demonstrated the efficacy of RME in the transverse gain of the maxilla through different pre and postoperative measurement processes using sagittal, coronal and axial planes given by CBCT scan so that numerous measures can be obtained through linear records, angulations between planes and surface areas [19][20][21][33][34][35]. However, despite the use of CBCT technology that allows for the three-dimensional analysis of cranial structures, to our knowledge there are no studies that measure the maxillary volume obtained after RME procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have analyzed the dento-skeletal [10] and morphological outcomes [11] of RME procedures using a computed tomography (CT) scan [12] or cone-beam computed tomography (CBCT) scan [4], and highlighted both width and depth increasing of the maxilla and also an increase in the inclination of the dentoalveolar process after RME procedures [1,[13][14][15][16][17]. In addition, the maxillary expansion after RME procedures has also been quantified by linear [18] and angular measurements [19] and even by analyzing the area of the palate surface [20][21][22][23]. However, Marini et al reported that the palatal volume increases in patients treated with RME procedures and recommended the application of three-dimensional (3D) measurement techniques to evaluate the skeletal changes [2].…”
Section: Introductionmentioning
confidence: 99%
“…With respect to transverse dimension, constricted arch problems have been solved through expansion, with increments in arch dimensions having been clearly demonstrated. [ 1 , 2 ] Mandibular expansion has not been recommended because the maxilla has a mid-palatal suture, [ 3 ] unlike the mandible. [ 4 ] A variety of methods such as the Schwarz and Bi-Helix appliances have been used, with limited dimension change and questionable expansion of the effective space primarily due to the inclination of teeth.…”
Section: Introductionmentioning
confidence: 99%